API 5L X65: influência do processo de soldagem mig térmico sobre a dureza e a mudança de fases na ZGG - Paiva Filho, Reginaldo Florêncio de (2019)
The developments in the welding process double pulsed MIG / MAG came to align a better quality of welding, better visual aspects of wires and high efficiency of pulsed MIG process; better ability of puddle control in the pulsed TIG (Tungsten inert gas) welding process. However, the heat pulsed MIG/MAG welding also causes in the HAZ - Heat affected Zone (ZTA) a rapid thermal heating and cooling cycles that results changes in metallurgical and mechanical properties. In this area although the material has not melted, solid-state phase transformations, recrystallization and grain growth may still occur as precipitations or dissolutions of substances present in the material as well. This phenomenon happens in certain temperatures. The present academic work investigates the influence of the double pulsed MIG / MAG variants (thermal) on the grain refinement of the microstructure of the API 5L X65 HAZ (ZTA) steel. The double Pulsed MIG variant was compared to the Conventional MIG and Pulsed MIG processes within two energy levels: 0.65 kJ / mm and 1.3kJ / mm for single wire welding at 1G position. As variants of response we analyzed microstructures (phases and grain sizes) and the hardness of heat zone affected (ZTA). Analysis of wire geometry, micro-hardness, grain size and phase identification by scanning electron microscopy (SEM) indicated that the Pulsed Double MIG (Thermal) variant has a better performance in HAZ (ZTA) grain refinement among the welding modes tested mainly with smaller grain size, higher hardness and phases that possibly indicate better mechanical properties in the region of coarse grains (ZGG) compared to other variants (Conventional and Pulsed).